PENINGKATAN KEMAMPUAN METAKOGNITIF UNTUK PENGEMBANGAN PROBLEM SOLVING SISWA MELALUI PROSES PEMBELAJARAN - Sari, Silvi Nur Laila; Margareta, Bela; Jariyah, Ita Ainun (Universitas Tanjungpura, 2024)
This study aims to understand the increase in metacognitive abilities for developing students' problem-solving through the learning process to provide deeper insight into effective learning strategies in helping students develop these abilities. The method used in this writing is a literature review with a qualitative approach, which is carried out by selecting the topic to be reviewed, tracking and selecting appropriate or relevant articles, carrying out literature analysis and synthesis (synthesis matrix), and planning the writing of the review. Based on the theories studied, it is argued that increasing students' metacognitive abilities makes students better able to plan, monitor, and evaluate thought processes when facing problems. Meanwhile, implementing learning strategies that support structured metacognition can help students develop better problem-solving. This can be applied through a Problem-Solving learning model assisted by metacognitive LKPD with a collaborative method based on a review of previous research literature.